COMPETITIVE ADVANTAGE TO MEDIATE THE INFLUENCE OF PRODUCT INNOVATION AND ENTREPRENEURIAL ORIENTATION ON MARKETING PERFORMANCE IN SMALL AND MEDIUM INDUSTRY - Dahana, Raiza Nora; Indrawati, Nur Khusniyah; Mugiono, Mugiono (Jurnal Aplikasi Manajemen, 2021)
This study aims to analyze the effect of product innovation, entrepreneurial orientation, and competitive advantage on marketing performance; test the effect of product innovation and entrepreneurial orientation towards marketing performance through competitive advantage as a mediation variable. The sample in this study was 69 owners of small and medium industries bakery in Ponorogo Residence who had made innovations on their products. The sampling technique in this study uses total sampling. Data analysis techniques used the approach Partial Least Squares (PLS). The results found that product innovation has a direct positive effect on marketing performance, entrepreneurial orientation has a direct positive effect on marketing performance, product innovation has a direct positive effect on competitive advantage, entrepreneurial orientation has a direct positive effect on competitive advantage, competitive advantage has a direct positive effect on marketing performance, product innovation has a positive effect on marketing performance through competitive advantage, and entrepreneurial orientation has a positive effect on marketing performance through competitive advantage. Competitive advantage acts as a partial mediating variable.